Safe and Sustainable Tall Buildings - State of the Art - Mendis, P. (Civil Engineering Dimension, 2012)
Tall buildings are becoming very popular around the world. Asia will have most of the tall buildings in this century. Both safety and sustainability aspects are important in planning and designing these buildings. The design and construction of tall buildings present many challenges for the design team, from engineers, architect through to the builder. Although structural systems could be developed and construction solutions could be found to design and construct very tall buildings in excess of 1 km (even 1 mile), other aspects such as fire and egress, long-term movements, environmental wind and perception of motion (including damping for dynamic effects), transportation (lifts) issues, sustainability, durability and maintenance will govern and may even restrict the heights. Current practices and important issues related to design of safe and sustainable design of tall buildings are discussed in this paper.